Społeczne znaczenie publicznych funkcji lasu – pożądany dla rekreacji i wypoczynku model drzewostanu i lasu - Gołos, Piotr (Leśne Prace Badawcze, 2010)
This publication presents the results of the investigation conducted in the years 1998–2006 with the goal to study social preferences and expectations towards selected public forest services as well as to define stand and forest characteristics as desired for a place of relaxation and recreation on the base of verbal descriptions and photographs presented by respondents. Questionnaires were presented to forest visitors in four Forest Promotional Complexes (LKP) and to the residents of the Podlaskie province (agricultural region) and of the Śląskie province (industrial region). In Łódź the city residents were interviewed within the area of the largest in Europe forest complex located inside the city boundaries (Łagiewnicki Forest), and in Warsaw within urban forests surrounding the capital. According to responces of respondents, the most important forest function is air protection, and the next important is the role of the forest as habitat for plants and animals. Forest recreation was recognized on the third place of the social significance of public forest functions and its management.The characteristics of the forest desirable for recreation included the following: forest should be tall, old, with the large amount of light reaching the green ground cover of the forest, with mixed species composition and rich forest ground cover. The comparison of the stand and forest model created from the verbal descriptions only in several cases was supported by pictures reflecting various stand types, which were presented during the photographic part of the survey.